Block copolymer–nanodiamond coassembly in solution: towards multifunctional hybrid materials. Issue 3 (5th January 2021) - Sutisna, Burhannudin; Janssens, Stoffel D.; Giussani, Alessandro; Vázquez-Cortés, David; Fried, Eliot
Abstract : Coassembly between block copolymers and nanodiamonds (NDs) leads to transparent UV-protective coatings and hybrid superstructures with hierarchical assembly of NDs. Abstract : Polymer–nanodiamond composites are excellent candidates for the fabrication of multifunctional hybrid materials. They integrate polymer flexibility and exceptional properties of nanodiamonds (NDs), such as biocompatibility, mechanical strength, color centers, and chemically-tailored surfaces. However, their development is hindered by the challenge of ensuring that NDs are homogeneously distributed in the composites. Here, we exploit colloidal coassembly between poly(isoprene- b -styrene- b -2-vinyl pyridine) (ISV) block copolymers (BCPs) and NDs to avoid ND self-agglomeration and direct ND spatial distribution. NDs were first air oxidized at 450 °C to obtain stable dispersions in dimethylacetamide (DMAc). By adding ISV into the dispersions, patchy hybrid micelles were formed due to H-bonds between NDs and ISV. The ISV–ND coassembly in DMAc was then used to fabricate nanocomposite films with a uniform sub-50 nm ND distribution, which has never been previously reported for an ND loading ( ϕ ND ) of more than 50 wt%. The films exhibit good transparency due to their well-defined nanostructures and smoothness and also exhibit an improved UV-absorption and hydrophilicity compared to neat ISV. More intriguingly, at a ϕ ND of 22 wt%, ISV and NDs coassemble into a network-like superstructure with well-aligned ND strings via a dialysis method. Transmission electron microscopy and dynamic light scattering measurements suggest a complex interplay between polymer–polymer, polymer–solvent, polymer–ND, ND–solvent, and ND–ND interactions during the formation of structures. Our work may provide an important foundation for the development of hierarchically ordered nanocomposites based on BCP–ND coassembly, which is beneficial for a wide spectrum of applications from biotechnology to quantum devices.